2016
DOI: 10.24264/icams-2016.iv.8
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Collagen from By-products, Designed to Increase the Quantity and Quality of Production in Agriculture

Abstract: Collagen polydispersions obtained by associated thermal and enzymatic processes for high-yield extraction of collagen from waste, under mild reaction conditions, are fit for application in agriculture. This study presents the possibility of using thermal and enzymatic processes of byproducts from fishing industry to obtain collagen extracts, to increase the quantity and quality of oilseeds and horticultural production. Collagen polydispersions were characterized by chemical and instrumental analyses: gravimetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Niculescu et al [11], reported that the collagen films were hydrophilic and favourable to water absorption. They noted that the contact angle of the water with the collagen film is lower compared to bovine collagen which exhibit moderate hydrophilicity.…”
Section: Introductionmentioning
confidence: 99%
“…Niculescu et al [11], reported that the collagen films were hydrophilic and favourable to water absorption. They noted that the contact angle of the water with the collagen film is lower compared to bovine collagen which exhibit moderate hydrophilicity.…”
Section: Introductionmentioning
confidence: 99%